License Plate Detection of Myanmar Vehicle Images from Dissimilar Angle Conditions - Khin, Ohnmar; Phothisonothai, Montri; Choomchuay, Somsak (My University, 2018)
It has been studied that there is no established LPR (License Plate Recognition) to detect and identify the license plates from dissimilar angles. The aim of the paper is to detect the dissimilar angles of the license plate with the non-fixed LPR system. Therefore, the horizontal and vertical dilation, skew angle detection and automatic bounding box have been proposed to detect the license plate. The proposed method has been applied to the four different types of Myanmar license plates, e.g., private cars, taxi, tour buses and religion cars. One car each is taken into four different types of angles on the dissimilar conditions. Experimental result indicated that this method can detect the disparate types of license plates with a high accuracy, i.e., the proposed approach achieved a favorable outcome rate of 97% at 100 license plates.
Keywords: bounding box; horizontal and vertical dilation; number plate detection; skew angle detection